ANALISIS PENGARUH VARIABEL DER, NPM DAN ROE TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR KEUANGAN - La Ode Rahmat Putra Rustaman (IQTISHADUNA, 2021)
Abstract: The main purpose of trading for the investors in capital market is a profit. This study aims to analyze the influence of fundamental factors such as debt to equity ratio, net profit margin, and return on equity on stock price. This study uses annual sample with the data from 2013-2018. Population of this research is 7 Factories, yet getting 7 factories after passing through the purposive sampling. This study uses analysis techniques of linear regression multiple which is a technique for knowing the entanglement of fundamental variables in the company to stock price in financial sector. The results of the study show that model of linear multiple regression equation is LN_Stock Price (Y) = 8,067 – 0,145 Debt to Equity Ratio + 4,759 Net Profit Margin + 1,961 Return On Equity and adjusted R2 value of 67,2 percent. Simultaneously these variable debt to equity ratio, net profit margin, and return on equity are significant to stock price, can be observed in value of probability is 0,000 < 0.05. Whereas, partially these variables debt to equity ratio and net profit margin have effects significantly on stock price as well as return on equity have effects insignificant on stock price all the same. Keywords : Fundamental Factors, Debt to Equity (DER), Net Profit Margin (NPM), Return on Equity (ROE), Stock Prices.